Evaluation of alternative vaccination routes against paratuberculosis in goats - Miguel Criado; Miguel Criado; Marta Silva; Marta Silva; Noive Arteche-Villasol; Noive Arteche-Villasol; David Zapico; David Zapico; Natalia Elguezabal; Elena Molina; José Espinosa; José Espinosa; et al. (Frontiers in Veterinary Science)
Paratuberculosis is a chronic granulomatous enteritis, caused by Mycobacterium avium subspecies paratuberculosis (Map), that affects ruminants worldwide. Vaccination has been considered the most cost-effective method for the control of this disease in infected dairy herds. However, currently available vaccines do not provide complete protection and interfere with the diagnosis of both paratuberculosis and bovine tuberculosis, limiting its use. Because of that, efforts are being made for the development of new vaccines. The primary objective of this study was to evaluate the efficacy of two whole-cell inactivated experimental vaccines against paratuberculosis in goats, administered through the oral (OV) and intradermal (IDV) routes, and compare them with that of the commercial subcutaneous vaccine Gudair® (SCV). Over an 11-month period, the effect of vaccination and a subsequent Map challenge on the specific peripheral immune responses and Map-DNA fecal shedding were recorded. At the end of the experiment, tissue bacterial load and lesion severity were assessed. The experimental vaccines did not induce specific humoral immune responses and only elicited mild and delayed cellular immune responses. Although the OV reduced lesion severity, neither this vaccine nor the IDV prototype was able to reduce fecal shedding or tissue bacterial load. Moreover, although the SCV did not confer sterile immunity, it outperformed both experimental vaccines in all these parameters.